Single-Dose Ibuprofen-Arginine as a Preventive for Pain, Edema, and Trismus After Impacted Lower Third Molar Surgery: A Randomized Split-Mouth Clinical Trial - Ramos, Edith Umasi; Benetti, Luan Pier; Oliveira, Júlio César Silva; Bassi, Ana Paula Farnezi (European Journal of Dentistry, 2021)
Objective We examined if the association of ibuprofen with arginine has a better anti-inflammatory effect on pain, edema, and trismus after surgery of the impacted mandibular third molar than ibuprofen alone.Materials and Methods The study included 21 patients, 18 to 30 years of age, each with an impacted, and bilateral and symmetric third molar (total n = 21) that required transalveolar extraction. Patients were randomly assigned numbers from 1 to 21. Group A received ibuprofen-arginine as preoperative medication, while Group B received only ibuprofen. Both groups received the same postoperative medications: amoxicillin + acetaminophen. All patients were evaluated for pain at 6, 12, and 24 hours. They were evaluated for edema and trismus before surgery; immediately after surgery; and at 24, 48, and 72 hours postoperatively. Postoperative pain scores used the visual analog scale (BS-11). For facial edema and trismus, linear measurements used the method modified by Gabka and Matsumura.Statistical Analysis For the evaluation of data between Group A and Group B, we used the statistical software SPSS version 22. The Shapiro-Wilk, analysis of variance, the Bonferroni comparisons, and the Wilcoxon test were used. All tests were based on a significance level of 0.05.Results The study results reveal that the facial edema scores of Group A and Group B presented statistically significant differences (p < 0.05), while for postoperative trismus, there was no statistically significant difference (p > 0.05) between the scores of Group A and Group B.Conclusion As a conclusion, we can state that the use of ibuprofen-arginine allows for significantly better control of pain and edema, and shows a tendency toward better recovery from trismus, although without statistical significance. Based on this, we can assert that arginine improves the anti-inflammatory power of ibuprofen, thus generating better tissue healing after surgery of the impacted third molar.
Keywords: arginine; ibuprofen; third molar; pain; edema